Implementation of multiple fan beam projection technique in optical fibre process tomography - Leong, Lai Chen (2005)
The application of optical sensors in process tomography involves using nonintrusive sensors to obtain vital information in order to produce images from the dynamic characteristics of a process system. The implementation of multiple fan beam projection technique is a novel approach in Optical Fibre Process Tomography using cost-effective optical fibre sensors with the aim to achieve a high data acquisition rate. For the thirty-two pairs of sensors used, the 2-projection and 4- projection techniques are being investigated. In comparison, the 4-projection technique yields better data acquisition rate, to more than 600 frames per second. In order to facilitate data acquisition process by controlling the operation of hardware interfacing in an efficient manner with less circuitry, low energy consumption and less heat dissipation, the PIC microcontroller and the sample and hold circuit are being used. Data obtained from optical fibre sensors will then be reconstructed into image using the Linear Back Projection and Iterative Reconstruction algorithms through Visual C++ programming. Concentration measurements from the reconstructed images are then used to obtain the mass flow rate of the solid/gas flow in a gravity flow rig. Series of error analyses show that the designed optical fibre sensors is feasible in performing as an instrument in solid flow visualization and as a mass flow rate meter, which is able to measure the mass flow rate at the range of not more than 40 percent of the plastic bead flow.